2020
DOI: 10.1021/jacs.0c01769
|View full text |Cite
|
Sign up to set email alerts
|

Splitting Mono- and Dibranched Alkane Isomers by a Robust Aluminum-Based Metal–Organic Framework Material with Optimal Pore Dimensions

Abstract: The separation of alkanes with different degrees of branching, particularly mono- and dibranched isomers, represents a challenging yet important industrial process for the production of premium gasoline blending components with high octane number. We report here the separation of linear/monobranched and dibranched alkanes through complete molecular sieving by a robust aluminum-based MOF material, Al-bttotb (H3bttotb = 4,4′,4″-(benzene-1,3,5-triyltris­(oxy))­tribenzoicacid). Single- and multicomponent adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…More recently, Yu et al reported the total separation of dibranched alkanes from their linear and monobranched isomers at ambient temperature and pressure by a rigid MOF, Al(bttotb) (H 3 bttotb = 4,4′,4″‐(benzene‐1,3,5‐triyltris(oxy))tribenzoicacid). [ 109 ] It has 1D channels with a diameter of ≈5.6 Å, comparable to the kinetic diameter of monobranched alkanes. The MOF adsorbs linear and monobranched hexanes with relatively fast kinetics at room temperature, but fully excludes dibranched 22DMB.…”
Section: Separation Of Alkane Isomersmentioning
confidence: 99%
“…More recently, Yu et al reported the total separation of dibranched alkanes from their linear and monobranched isomers at ambient temperature and pressure by a rigid MOF, Al(bttotb) (H 3 bttotb = 4,4′,4″‐(benzene‐1,3,5‐triyltris(oxy))tribenzoicacid). [ 109 ] It has 1D channels with a diameter of ≈5.6 Å, comparable to the kinetic diameter of monobranched alkanes. The MOF adsorbs linear and monobranched hexanes with relatively fast kinetics at room temperature, but fully excludes dibranched 22DMB.…”
Section: Separation Of Alkane Isomersmentioning
confidence: 99%
“…Accordingly, we then measured C 6 vapour adsorption at 30 °C and the results were shown in Figure 3e. Ultrahigh n-HEX adsorption capacity up to 209 mg/g was observed, exceeding most top level materials for this task [45][46][47][48][49][50][51][52][53] such as Al-bttotb (151 mg/g), 49 Ca-tcpb (150 mg/g), 48 MIL-53(Fe)-(CF 3 ) 2 (32 mg/g), 47 and Fe 2 (BDP) 3 (113 mg/g) 46 . By contrast, no adsorption and very low adsorption of 10.7 mg/g was observed for the dibranched isomers of 22DMB and 23DMB, owing to MS effect, since the kinetic diameter of dibranched isomers is far larger than the window of [Th 6 Co 2 ] cage.…”
Section: Resultsmentioning
confidence: 94%
“…In the literature, all reports are focused on the separation of C 6 vapour via multicomponent column breakthrough measurements. [45][46][47][48][49][50][51][52][53] From the viewpoint of saving energy, the direct separation of C 6 isomer from liquid mixture is more desirable, as these C 6 isomers are essentially liquid at room temperature with boiling point more than 58°. In each case, the activated Th-Co-Cage-1 samples were rst immersed in commercially binary mixture.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these materials are capable of separating monobranched alkanes and their dibranched isomers with high efficiency. We recently reported two MOF‐based splitters, Ca(H 2 tcpb) [14] and Al‐bttotb, [15] that separate monobranched and dibranched alkanes through selective molecular sieving. Nevertheless, they are both built on relatively complicated linkers, making their scale‐up synthesis difficult/expensive.…”
Section: Methodsmentioning
confidence: 99%